Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Millennial-scale fire and climate dynamics in the world's largest tropical wetland show emerging fire threat to flooded ecosystems - Bronwen S. Whitney; Danilo M. Neves; Nicholas J.D. Loughlin; Carlos D'Apolito; Carla Coblinski Tavares; Emma P. Hocking; Francis E. Mayle; Mitchell J. Power; Aguinaldo Silva; Mario L. Assine (Global and Planetary Change, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Waterfowl Move Less in Heterogeneous and Human‐Populated Landscapes, With Implications for Spread of Avian Influenza Viruses - Claire S. Teitelbaum; Diann J. Prosser; Joshua T. Ackerman; Sakib Ahmed; A. B. M. Sarowar Alam; Kazi Zenifar Azmiri; Nyambaya Batbayar; Joël Bêty; Abigail Blake‐Bradshaw; Dmitrijs Boiko; Nelleke H. Buitendijk; Jeffrey J. Buler; et al. (Ecology Letters, 2026)
Animal movements contribute to the spread of infectious diseases and are driven in part by environmental conditions. We investigated the links among the environment, animal movement, and infectious disease dynamics in waterfowl, which are among the primary wildlife hosts of avian influenza viruses. By combining telemetry data on 4606 individuals from 26 waterfowl species with data on land cover, weather, and vegetation, we found that waterfowl moved less in areas of higher land cover heterogeneity and higher human population density. Moreover, predicted waterfowl movement distances were weakly but positively correlated with distances between detections of H5N1 highly pathogenic avian influenza in wild waterfowl, suggesting that environmental conditions might contribute to the spread of this disease via their effects on bird movements. By considering wildlife movements alongside other drivers of infectious disease dynamics, such as livestock production and human mobility, we move closer to predicting outbreaks and informing interventions.

Fault timing and depocentre development in the northern Perth Basin during the evolution of the East Gondwana rift - Christopher Watts; Chris Elders; Mitchell O’Mara; Nicholas E. Timms; Hugo K.H. Olierook (Gondwana Research, 2025)

Dietetics and Nursing Students Affirmatively Report the Likelihood of Recommending Predominantly Plant-based Diets for Non-communicable Disease Management - P. Dyett; L. Foster-Nicholas; C. Mitchell; V. Jones-Oyefeso; V. Sealey-Tobias; A. Adams-Robinson; P. Valley-Thom; D. Balfour (Journal of the Academy of Nutrition and Dietetics, 2025)

Publisher Correction to: Quantifying intra-urban socio-economic and environmental vulnerability to extreme heat events in Johannesburg, South Africa - Craig Parker; Craig Mahlasi; Tamara Govindasamy; Lebohang Radebe; Nicholas Brian Brink; Christopher Jack; Madina Doumbia; Etienne Kouakou; Matthew Chersich; Guéladio Cissé; Sibusisiwe Makhanya; Aakin Bobola; et al. (International Journal of Biometeorology, 2025)

Quantifying intra-urban socio-economic and environmental vulnerability to extreme heat events in Johannesburg, South Africa - Craig Parker; Craig Mahlasi; Tamara Govindasamy; Lebohang Radebe; Nicholas Brian Brink; Christopher Jack; Madina Doumbia; Etienne Kouakou; Matthew Chersich; Guéladio Cissé; Sibusisiwe Makhanya; Aakin Bobola; et al. (International Journal of Biometeorology, 2025)
Urban populations face increasing vulnerability to extreme heat events, particularly in rapidly urbanising Global South cities where environmental exposure intersects with socioeconomic inequality and limited healthcare access. This study quantifies heat vulnerability across Johannesburg, South Africa, by integrating high-resolution environmental data with socio-economic and health metrics across 135 urban wards. We examine how historical urban development patterns influence contemporary vulnerability distributions using principal component analysis and spatial statistics. Environmental indicators (Land Surface Temperature (LST), vegetation indices, and thermal field variance) were combined with socioeconomic and health variables (including indicators on crowded dwellings and healthcare access, self-reporting of chronic diseases) in a comprehensive vulnerability assessment. Principal Component Analysis revealed three primary dimensions explaining 56.6% (95% CI: 52.4–60.8%) of the total variance: urban heat exposure (31.5%), health status (12.8%), and socio-economic conditions (12.3%). Built-up areas showed weak but significant correlations with heat indices (ρ = 0.28, p < 0.01), while higher poverty levels demonstrated moderate positive correlations with LST (ρ = 0.41, p < 0.001). The spatial analysis identified significant clustering of vulnerability (Global Moran's I = 0.42, p < 0.001), with distinct high-vulnerability clusters in historically disadvantaged areas. Alexandra Township showed the highest vulnerability(HVI score: 0.87, LST: 29.8 °C ± 0.4 °C, NDVI: 0.08 ± 0.02), with factors characterising the high vulnerability in that area including limited healthcare access and extreme heat exposure. Northern suburbs formed a significant low-vulnerability cluster (Mean HVI = 0.23 ± 0.07, p < 0.001), benefiting from greater vegetation coverage and better healthcare access. These findings demonstrate how historical planning decisions continue to shape contemporary environmental health risks, with vulnerability concentrated in areas of limited healthcare access and high extreme heat exposure. Results suggest the need for targeted interventions that address both environmental and social dimensions of heat vulnerability, particularly focusing on expanding healthcare access in identified hotspots and implementing community-scale green infrastructure in high-risk areas. This study provides an evidence-based framework for prioritising heat-resilience initiatives in rapidly urbanising Global South cities while highlighting the importance of addressing historical inequities in urban adaptation planning.

Temporal trends in ambient fine particulate matter in Grenada between 2009 and 2022 - Natalie Kuo-Hsuan Yang; Nicholas Dirienzo; Martin S. Forde; Paul J. Villeneuve; Andrea Sealy; Sabrina Compton; Kerry Mitchell (Environmental Monitoring and Assessment, 2025)

Mapping illegal trade routes of live cheetahs from the Horn of Africa to the Arabian Peninsula - Paul H. Evangelista; Nicholas E. Young; Darin K. Schulte; Patricia D. Tricorache; Matthew W. Luizza; Sarah M. Durant; Kelly W. Jones; Nicholas Mitchell; Tomas Maule; Abdullahi H. Ali; Redae T. Tesfai; Peder S. Engelstad (Conservation Biology, 2025)
Less than 7000 cheetahs ( Acinonyx jubatus ) persist in Africa. Although human–wildlife conflict, habitat degradation, and loss of prey are major threats to cheetah populations, illegal trade in live cubs for pets may have the most significant impact on populations in the Horn of Africa. We developed a novel, stepwise decision support tool to predict probable trafficking routes by leveraging the power of distinct modeling approaches. First, we created a cheetah habitat suitability index (HSI) to determine where source cheetah populations may occur. We then created a trafficking network model linking known and predicted cheetah populations with documented destinations in the Arabian Peninsula. A significant area in Eastern Ethiopia and Northern Somalia was estimated to harbor undocumented cheetahs. When these predicted populations were used as a supply source, the trafficking network model showed multiple routes passing through Somaliland and across the Gulf of Aden to Yemen, supporting the notion that undocumented cheetahs may be supplying pet market demands. Though we demonstrate how our decision support tool can inform law enforcement, conservation strategies, and community engagement, we caution that our results are not fully validated due to limited accessibility, alternative trafficking routes, and the cryptic nature of illegal wildlife trade.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

The murine metastatic microenvironment of experimental brain metastases of breast cancer differs by host age in vivo: a proteomic study - Allison L. Hunt; Imran Khan; Alex M. L. Wu; Sasha C. Makohon-Moore; Brian L. Hood; Kelly A. Conrads; Tamara Abulez; Jonathan Ogata; Dave Mitchell; Glenn Gist; Julie Oliver; Debbie Wei; et al. (Clinical & Experimental Metastasis, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Applying the ‘Candidacy’ Model to understand access to key nutrition, food & health services in LMIC contexts: a qualitative study in Odisha, India - Rebecca Mitchell; Jessica Gordon; Gopal Krushna Bhoi; Nicholas Nisbett (Food Security, 2023)
In order to make progress towards Sustainable Development Goal 2 – Zero Hunger - we must acquire a better understanding of what continues to hamper achieving food security, particularly in contexts where progress has been achieved, but has then faltered. This article investigates access to nutrition and food services in three of the Indian state of Odisha’s traditionally poorer districts, where a large number of the state’s most marginalised populations live. Semi-structured interviews were carried out in 11 villages. The Dixon-Woods Candidacy Model was employed to provide greater insight into the experiences of access to health and nutrition services, from both the supply and the demand sides. We found that there are many points along the journey that hamper access. We identified two levels of gatekeepers that can create (or remove) barriers, the first as front-line service providers and the second as high-level officials. The candidacy model shows that marginalisation caused by identity, poverty and education disparities hampers progress throughout this journey. This article aims to provide a view to improve our understanding of access to health, food and nutrition services, to improve food security, and to show the value of the candidacy model applied to an LMIC health setting.

Methyl methacrylate thermal decomposition: Modeling and laser spectroscopy of species time-histories behind reflected shock waves - Isabelle C. Sanders; Nicholas M. Kuenning; Nicolas Q. Minesi; Daniel I. Pineda; R. Mitchell Spearrin (Fuel, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Climate drivers of adult insect activity are conditioned by life history traits - Michael W. Belitz; Vijay Barve; Joshua R. Doby; Maggie M. Hantak; Elise A. Larsen; Daijiang Li; Jessica A. Oswald; Neeka Sewnath; Mitchell Walters; Narayani Barve; Kamala Earl; Nicholas Gardner; et al. (Ecology Letters, 2021)
Insect phenological lability is key for determining which species will adapt under environmental change. However, little is known about when adult insect activity terminates and overall activity duration. We used community‐science and museum specimen data to investigate the effects of climate and urbanisation on timing of adult insect activity for 101 species varying in life history traits. We found detritivores and species with aquatic larval stages extend activity periods most rapidly in response to increasing regional temperature. Conversely, species with subterranean larval stages have relatively constant durations regardless of regional temperature. Species extended their period of adult activity similarly in warmer conditions regardless of voltinism classification. Longer adult durations may represent a general response to warming, but voltinism data in subtropical environments are likely underreported. This effort provides a framework to address the drivers of adult insect phenology at continental scales and a basis for predicting species response to environmental change.

Workflow for the Generation of Expert-Derived Training and Validation Data: A View to Global Scale Habitat Mapping - Chris M. Roelfsema; Mitchell Lyons; Nicholas Murray; Eva M. Kovacs; Emma Kennedy; Kathryn Markey; Rodney Borrego-Acevedo; Alexandra Ordoñez Alvarez; Chantel Say; Paul Tudman; Meredith Roe; Jeremy Wolff; et al. (Frontiers in Marine Science, 2021)
Our ability to completely and repeatedly map natural environments at a global scale have increased significantly over the past decade. These advances are from delivery of a range of on-line global satellite image archives and global-scale processing capabilities, along with improved spatial and temporal resolution satellite imagery. The ability to accurately train and validate these global scale-mapping programs from what we will call “reference data sets” is challenging due to a lack of coordinated financial and personnel resourcing, and standardized methods to collate reference datasets at global spatial extents. Here, we present an expert-driven approach for generating training and validation data on a global scale, with the view to mapping the world’s coral reefs. Global reefs were first stratified into approximate biogeographic regions, then per region reference data sets were compiled that include existing point data or maps at various levels of accuracy. These reference data sets were compiled from new field surveys, literature review of published surveys, and from individually sourced contributions from the coral reef monitoring and management agencies. Reference data were overlaid on high spatial resolution satellite image mosaics (3.7 m × 3.7 m pixels; Planet Dove) for each region. Additionally, thirty to forty satellite image tiles; 20 km × 20 km) were selected for which reference data and/or expert knowledge was available and which covered a representative range of habitats. The satellite image tiles were segmented into interpretable groups of pixels which were manually labeled with a mapping category via expert interpretation. The labeled segments were used to generate points to train the mapping models, and to validate or assess accuracy. The workflow for desktop reference data creation that we present expands and up-scales traditional approaches of expert-driven interpretation for both manual habitat mapping and map training/validation. We apply the reference data creation methods in the context of global coral reef mapping, though our approach is broadly applicable to any environment. Transparent processes for training and validation are critical for usability as big data provide more opportunities for managers and scientists to use global mapping products for science and conservation of vulnerable and rapidly changing ecosystems.

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

A global coral reef probability map generated using convolutional neural networks - Jiwei Li; David E. Knapp; Nicholas S. Fabina; Emma V. Kennedy; Kirk Larsen; Mitchell B. Lyons; Nicholas J. Murray; Stuart R. Phinn; Chris M. Roelfsema; Gregory P. Asner (Coral Reefs, 2020)

JA:2021-12. How to Increase ATV Safe Riding Behaviors in Youth: FFA Members from across the Country Respond - Charles Jennissen; Nicholas Stange; Cole Wymore; Mitchell Hooyer; Pam Hoogerwerf; Lauren Mulford; Gerene Denning (Journal of Agromedicine, 2020)

Strain-specificity in the hydrogen sulphide signalling network following dietary restriction in recombinant inbred mice - Stephen E. Wilkie; Lorna Mulvey; William A. Sands; Diana E. Marcu; Roderick N. Carter; Nicholas M. Morton; Christopher Hine; James R. Mitchell; Colin Selman (GeroScience, 2020)
Modulation of the ageing process by dietary restriction (DR) across multiple taxa is well established. While the exact mechanism through which DR acts remains elusive, the gasotransmitter hydrogen sulphide (H 2 S) may play an important role. We employed a comparative-type approach using females from three ILSXISS recombinant inbred mouse strains previously reported to show differential lifespan responses following 40% DR. Following long-term (10 months) 40% DR, strain TejJ89—reported to show lifespan extension under DR—exhibited elevated hepatic H 2 S production relative to its strain-specific ad libitum (AL) control. Strain TejJ48 (no reported lifespan effect following 40% DR) exhibited significantly reduced hepatic H 2 S production, while H 2 S production was unaffected by DR in strain TejJ114 (shortened lifespan reported following 40% DR). These differences in H 2 S production were reflected in highly divergent gene and protein expression profiles of the major H 2 S production and disposal enzymes across strains. Increased hepatic H 2 S production in TejJ89 mice was associated with elevation of the mitochondrial H 2 S-producing enzyme 3-mercaptopyruvate sulfurtransferase (MPST). Our findings further support the potential role of H 2 S in DR-induced longevity and indicate the presence of genotypic-specificity in the production and disposal of hepatic H 2 S in response to 40% DR in mice.

Do sounds near the hand facilitate tactile reaction times? Four experiments and a meta-analysis provide mixed support and suggest a small effect size - Nicholas Paul Holmes; Dennis Martin; William Mitchell; Zeeshan Noorani; Amber Thorne (Experimental Brain Research, 2020)
The brain represents the space immediately surrounding the body differently to more distant parts of space. Direct evidence for this ‘peripersonal space’ representation comes from neurophysiological studies in monkeys, which show distance-dependent responses to visual stimuli in neurons with spatially coincident tactile responses. Most evidence for peripersonal space in humans is indirect: spatial- and distance-dependent modulations of reaction times and error rates in behavioural tasks. In one task often used to assess peripersonal space, sounds near the body have been argued to speed reactions to tactile stimuli. We conducted four experiments attempting to measure this distance-dependent audiotactile interaction. We found no distance-dependent enhancement of tactile processing in error rates or task performance, but found some evidence for a general speeding of reaction times by 9.5 ms when sounds were presented near the hand. A systematic review revealed an overestimation of reported effect sizes, lack of control conditions, a wide variety of methods, post hoc removal of data, and flexible methods of data analysis. After correcting for the speed of sound, removing biased or inconclusive studies, correcting for temporal expectancy, and using the trim-and-fill method to correct for publication bias, meta-analysis revealed an overall benefit of 15.2 ms when tactile stimuli are accompanied by near sounds compared to sounds further away. While this effect may be due to peripersonal space, response probability and the number of trials per condition explained significant proportions of variance in this near versus far benefit. These confounds need to be addressed, and alternative explanations ruled out by future, ideally pre-registered, studies.

A targeted genotyping-by-sequencing tool (Rapture) for genomics-assisted breeding in oat - Wubishet A. Bekele; Asuka Itaya; Brian Boyle; Weikai Yan; Jennifer Mitchell Fetch; Nicholas A. Tinker (Theoretical and Applied Genetics, 2020)

Mapping of the stem rust resistance gene Pg13 in cultivated oat - Aida Z. Kebede; Belayneh Admassu-Yimer; Wubishet A. Bekele; Tyler Gordon; J. Michael Bonman; Ebrahiem Babiker; Yue Jin; Sam Gale; Charlene P. Wight; Nicholas A. Tinker; Jim G. Menzies; Aaron D. Beattie; et al. (Theoretical and Applied Genetics, 2020)

Identification of a Bipolar Disorder Vulnerable Gene CHDH at 3p21.1 - Hong Chang; Lingyi Li; Tao Peng; Maria Grigoroiu-Serbanescu; Sarah E. Bergen; Mikael Landén; Christina M. Hultman; Andreas J. Forstner; Jana Strohmaier; Julian Hecker; Thomas G. Schulze; Bertram Müller-Myhsok; et al. (Molecular Neurobiology, 2017)

Fixed versus sun tracking solar panels: an economic analysis - Bahram Asiabanpour; Zaid Almusaied; Semih Aslan; Marcus Mitchell; Eric Leake; Heejoo Lee; Jesus Fuentes; Kyle Rainosek; Nicholas Hawkes; Andrew Bland (Clean Technologies and Environmental Policy, 2017)

Revealing pMDI Spray Initial Conditions: Flashing, Atomisation and the Effect of Ethanol - Nicholas Mason-Smith; Daniel J. Duke; Alan L. Kastengren; Daniela Traini; Paul M. Young; Yang Chen; David A. Lewis; Daniel Edgington-Mitchell; Damon Honnery (Pharmaceutical Research, 2017)

Convergent Lines of Evidence Support LRP8 as a Susceptibility Gene for Psychosis - Ming Li; Liang Huang; Maria Grigoroiu-Serbanescu; Sarah E. Bergen; Mikael Landén; Christina M. Hultman; Andreas J. Forstner; Jana Strohmaier; Julian Hecker; Thomas G. Schulze; Bertram Müller-Myhsok; Andreas Reif; et al. (Molecular Neurobiology, 2016)

Primate genotyping via high resolution melt analysis: rapid and reliable identification of color vision status in wild lemurs - Rachel L. Jacobs; Amanda N. Spriggs; Tammie S. MacFie; Andrea L. Baden; Mitchell T. Irwin; Patricia C. Wright; Edward E. Louis; Richard R. Lawler; Nicholas I. Mundy; Brenda J. Bradley (Primates, 2016)

Last interglacial (MIS 5e) sea-level determined from a tectonically stable, far-field location, Eyre Peninsula, southern Australia - C. V. Murray-Wallace; A. P. Belperio; A. Dosseto; W. A. Nicholas; C. Mitchell; R. P. Bourman; S. M. Eggins; R. Grün (Australian Journal of Earth Sciences, 2016)

Insights into Spray Development from Metered-Dose Inhalers Through Quantitative X-ray Radiography - Nicholas Mason-Smith; Daniel J. Duke; Alan L. Kastengren; Peter J. Stewart; Daniela Traini; Paul M. Young; Yang Chen; David A. Lewis; Julio Soria; Daniel Edgington-Mitchell; Damon Honnery (Pharmaceutical Research, 2016)

Temporally and Spatially Resolved x-ray Fluorescence Measurements of in-situ Drug Concentration in Metered-Dose Inhaler Sprays - Daniel J. Duke; Alan L. Kastengren; Nicholas Mason-Smith; Yang Chen; Paul M. Young; Daniela Traini; David Lewis; Daniel Edgington-Mitchell; Damon Honnery (Pharmaceutical Research, 2016)

Cage Versus Noncage Laying-Hen Housings: Worker Respiratory Health - Diane Mitchell; Veronica Arteaga; Tracey Armitage; Frank Mitloehner; Daniel Tancredi; Nicholas Kenyon; Marc Schenker (Journal of Agromedicine, 2015)

A blood spot method for detecting fumonisin-induced changes in putative sphingolipid biomarkers in LM/Bc mice and humans - Ronald T. Riley; Jency L. Showker; Christine M. Lee; Cody E. Zipperer; Trevor R. Mitchell; Kenneth A. Voss; Nicholas C. Zitomer; Olga Torres; Jorge Matute; Simon G. Gregory; Allison E. Ashley-Koch; Joyce R. Maddox; et al. (Food Additives & Contaminants: Part A, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Effectiveness of subsurface pressure monitoring for brine leakage detection in an uncertain CO2 sequestration system - Nicholas A. Azzolina; Mitchell J. Small; David V. Nakles; Grant S. Bromhal (Stochastic Environmental Research and Risk Assessment, 2014)

Isolation of human lymphatic malformation endothelial cells, their in vitro characterization and in vivo survival in a mouse xenograft model - Zerina Lokmic; Geraldine M. Mitchell; Nicholas Koh Wee Chong; Jacqueline Bastiaanse; Yi-Wen Gerrand; Yiping Zeng; Elizabeth D. Williams; Anthony J. Penington (Angiogenesis, 2014)

Big claims for big weights but with little evidence - Nicholas A. Burd; Daniel R. Moore; Cameron J. Mitchell; Stuart M. Phillips (European Journal of Applied Physiology, 2013)

Genetic markers of ovarian follicle number and menopause in women of multiple ethnicities - Sonya M. Schuh-Huerta; Nicholas A. Johnson; Mitchell P. Rosen; Barbara Sternfeld; Marcelle I. Cedars; Renee A. Reijo Pera (Human Genetics, 2012)

Effects of acute administration of nicotine, amphetamine, diazepam, morphine, and ethanol on risky decision-making in rats - Marci R. Mitchell; Colin M. Vokes; Amy L. Blankenship; Nicholas W. Simon; Barry Setlow (Psychopharmacology, 2011)

Synthesis and biological evaluation of a novel anti-malarial lead - Nicholas L. Hammond; Seoung-ryoung Choi; Paulo Carvalho; Hua Liu; Shabana Khan; Mitchell A. Avery (Medicinal Chemistry Research, 2011)

Moderate Ethanol Preconditioning of Rat Brain Cultures Engenders Neuroprotection Against Dementia-Inducing Neuroinflammatory Proteins: Possible Signaling Mechanisms - Michael A. Collins; Edward J. Neafsey; Kewei Wang; Nicholas J. Achille; Robert M. Mitchell; Sreevidya Sivaswamy (Molecular Neurobiology, 2010)

Combining plant resistance and a natural enemy to control Amphorophora idaei - Carolyn Mitchell; Scott N. Johnson; Stuart C. Gordon; A. Nicholas E. Birch; Stephen F. Hubbard (BioControl, 2010)

Trends in landslide occurrence in Nepal - David N. Petley; Gareth J. Hearn; Andrew Hart; Nicholas J. Rosser; Stuart A. Dunning; Katie Oven; Wishart A. Mitchell (Natural Hazards, 2007)

Mapping the central effects of ketamine in the rat using pharmacological MRI - Clare L. Littlewood; Nicholas Jones; Michael J. O’Neill; Stephen N. Mitchell; Mark Tricklebank; Steven C. R. Williams (Psychopharmacology, 2006)

Mapping the central effects of ketamine in the rat using pharmacological MRI - Clare L. Littlewood; Nicholas Jones; Michael J. O’Neill; Stephen N. Mitchell; Mark Tricklebank; Steven C. R. Williams (Psychopharmacology, 2006)

Surprisingly minor influence of TRAV11 (Vα14) polymorphism on NK T-receptor mCD1/α-galactosylceramide binding kinetics - Bee-Cheng Sim; Kaisa Holmberg; Stephane Sidobre; Olga Naidenko; Nathalie Niederberger; Shane D. Marine; Mitchell Kronenberg; Nicholas R. J. Gascoigne (Immunogenetics, 2003)

A study of females with deletions of the short arm of the X chromosome - Rowena S. James; Brian Coppin; Paola Dalton; Nicholas R. Dennis; Caroline Mitchell; Andrew J. Sharp; David H. Skuse; N. Simon Thomas; P. A. Jacobs (Human Genetics, 1998)